The effect of self-directed online metacognitive listening practice on Chinese EFL learners' listening ability, metacognition, and self-efficacy - Pei, Tao; Suwanthep, Jitpanat; Lu, Huashan (Frontiers in Psychology, 2023)
In the past decades, there has been a growing body of research on metacognitive listening instruction using the Metacognitive Pedagogical Cycle (MPC). However, previous research into the effect of metacognitive instruction on L2 listening, metacognition, and self-efficacy has yielded inconclusive findings. Besides, few studies have examined the effects of integrating MPC with technology. To fill this gap, we developed a self-directed online listening practice based on the MPC and investigated its effect on Chinese intermediate EFL learners' listening comprehension, metacognitive awareness, and self-efficacy. We conducted a mixed-method study with two groups of learners for 14 weeks: an experimental group that used the online metacognitive listening practice and a control group that used traditional listening practice without focusing on metacognitive awareness. Multiple data sources from listening tests, questionnaires, reflective notes, and interviews were used to triangulate the findings. The results showed that online metacognitive listening practice could improve learners' listening comprehension. However, there was little evidence that the training increased metacognitive awareness and listening self-efficacy. 1 Commented [2]: Add Chinese EFL learners Commented [3]: Rephrase the independent variable Commented [4]: Indicate the average age.